Why the Influence of Women on Boards Still Lags - Whitler, Kimberly; Henretta, Deborah; Fournier, Susan; Avery, Jill; Colony, George; Danneels, Erwinn; Eccles, Robert (MIT Sloan Management Review, 2018)
Research indicates that the reason women aren't making more rapid inroads on corporate boards is that few have reached the most influential board leadership positions. Although more women are on boards now than 10 years ago, very few have been promoted to a post that would give them influence beyond their seat at the table.